STUDI PERBANDIGAN TEKANAN LATERAL TANAH SEDANG DAN TANAH AMAT LUNAK - Alexandro Kevin Wijaya; Chaidir Anwar Makarim (JMTS: Jurnal Mitra Teknik Sipil, 2022)
Indonesia is a country consisting of thousands of islands and different geographical conditions. Soil conditions in Indonesia have different characteristics. Soil is made up of minerals and organic materials. The distribution of very soft soil in Indonesia is quite large, but it is rarely discussed and even questioned, so that it can cause construction failure. It turns out that the nature of the very soft soil is different from the nature of the soil in general. Very soft soil has soil properties that tend to be like 'thick water' like slurry that flows freely compared to soil in general. In this study, an analysis of the comparison of the lateral pressure of the soil on medium and very soft soils will be carried out, without paying attention to external loads. This is done by comparing the lateral pressure of the soil when the soil is at rest, the active and passive states when the soil is moderate and the soil is very soft for each soil layer. The analysis of the results of mathematical calculations is entered into a geotechnical-based program for lateral soil deformation. The results of the analysis of the calculation of the lateral stress and pressure of the soil, it was found that the lateral pressure of the soil in the very soft soil is greater than the stress and the lethal pressure of the soil in the medium soil, and the resulting deformation of the very soft soil layer is greater than the result of the medium soil layer. Indonesia merupakan negara yang terdiri dari beribu-ribu pulau dan kondisi geografis yang berbeda-beda pula. Kondisi tanah di Indonesia memiliki karakteristik yang berbeda-beda. Tanah sendiri terbentuk dari mineral dan bahan-bahan organik. Sebaran tanah amat lunak di Indonesia lumayan banyak namun jarang dibahas bahkan dipermasalahkan, sehingga dapat menyebabkan kegagalan konstruksi. Ternyata sifat dari tanah amat lunak berbeda dengan sifat dari tanah pada umumnya. Tanah amat lunak memiliki sifat tanah yang cenderung seperti ‘air kental’ bagaikan bubur yang mengalir dengan bebas dibandingkan dengan tanah pada umunya. Pada peneilitian akan dilakukannya analisis perbandingan tekanan lateral tanah terhadap tanah sedang dan tanah amat lunak, dengan tidak memperhatikan beban yang berasal dari luar. Dilakukan dengan membandingakan tekanan lateral tanah pada saat tanah keadaan diam, keadaan aktif maupun pasif pada saat keadaan tanah sedang dan tanah amat lunak untuk setiap lapisan tanah. Analisis dari hasil perhitungan matematis dimasukan kedalam program berbasis geoteknik untuk defromasi lateral tanah. Hasil dari analaisi perhitungan tegangan dan tekanan lateral tanah didapakatkan tekanan lateral tanah pada keadaan tanah amat lunak lebih besar dibandingkan dengan tegangan maupaun tekanan leteral tanah pada keadaan tanah sedang, dan deformansi yang dihasilkan dari lapisan tanah amat lunak lebih besar dibandingan hasil dari lapisan tanah sedang.